Upinder Singh, A History of Ancient and Early Medieval India. From Stone Age to the 12th Century, Delhi, Pearson, 2009, 677 pp. - Melchor Hernández, Yver Alonso (Estudios de Asia y África, 2014)
Upinder Singh, A History of Ancient and Early Medieval India. From Stone Age to the 12th Century, Delhi, Pearson, 2009, 677 pp.